Review on the Future Grid -Microgrid - Singh, Fatehbir; Sharma, Sharad (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
The Microgrid concept using renewable energy sources is a building block towards the future energy networks for long-term viable solution of energy needs . Many microgrid developments carried out in several countries, because microgrid offers many advantages, including better power quality and more environmentally friendly. Microgrid development concern in technology generation, microgrid architecture, power electronics, control systems and protection systems. This paper provides a review on Microgrid system across the world.